2021
DOI: 10.3390/cancers13112824
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Low Breast Cancer: Molecular Characteristics and Prognosis

Abstract: Background: We aimed to determine the distribution of intrinsic subtypes within HER2-low breast cancer (BC), and to describe the prognostic impact of HER2-low status on survival outcomes. Methods: This is a retrospective, observational study of primary BC extracted from The Cancer Genome Atlas dataset. We described the distribution of PAM50 intrinsic subtypes within HER2-low BC subtype according to hormonal receptor status (positive (HR+) and negative (HR−)). Secondly, we assessed the impact of HER2-low on sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
163
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(191 citation statements)
references
References 42 publications
26
163
1
1
Order By: Relevance
“…This finding was also confirmed in a following study were we showed a significant positive correlation between ERBB2 mRNA levels and HER2 protein levels (Spearman Correlation ¼ 0.531, p < 0.001) [109]. Finally, we found no survival differences between HER2-low vs 0 tumors, however the large biological heterogeneity observed, confirmed by a following study based on TCGA data, might have potential therapeutic implications [108,110]. An exemplification of the correlation between HER2 protein and mRNA levels is reported in Fig.…”
Section: Beyond Her2 Overexpression: Her2-low Breast Tumors and Her2 Heterogeneitysupporting
confidence: 86%
“…This finding was also confirmed in a following study were we showed a significant positive correlation between ERBB2 mRNA levels and HER2 protein levels (Spearman Correlation ¼ 0.531, p < 0.001) [109]. Finally, we found no survival differences between HER2-low vs 0 tumors, however the large biological heterogeneity observed, confirmed by a following study based on TCGA data, might have potential therapeutic implications [108,110]. An exemplification of the correlation between HER2 protein and mRNA levels is reported in Fig.…”
Section: Beyond Her2 Overexpression: Her2-low Breast Tumors and Her2 Heterogeneitysupporting
confidence: 86%
“…Recently, Agostinetto et al evaluated the transcriptomic profile of the HER2-low group using the PAM50 intrinsic subtype classification and data on 804 primary breast cancers (n = 410 HER2 1+/2+ tumors, among which 74 were TNBC) from the TCGA dataset [ 12 ]. They found that the percentage of HER2-enriched tumors (i.e., hormone receptor-negative and HER2-positive) was higher in the HER2 1+/2+ TNBC group (13.7% versus 1.6% in the HER2 0 TNBC population), unlike the study by Schettini et al (9% of HER2-enriched tumors in the HER2 0 TNBC population vs. 7.1% in the HER2 1+/2+ TNBC population) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of anti-HER2 agents in HER2-low tumors has not been demonstrated yet [ 8 , 9 ], and this breast cancer subgroup is thought to have a poorer prognosis compared with HER2 0 tumors, based on retrospective studies. However, the published evidence shows conflicting results from one clinical setting to another one, and depending on hormone receptor status [ 8 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies also discovered that HER2-low/HR + patients had similar survival outcomes compared with HER2-/HR + patients. Furthermore, a recent research based on PAM50 subtype demonstrated that instead of low HER2 expression, it was hormone receptor and its related genes expression that might be the actually dominated oncological driver for HER2-low/HR + breast cancer 10 . This subtype was found to make up for a dominated proportion of luminal A/B breast cancer in current data.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies about these tumors were insu cient for clinicians to differentiate them from other traditional subtypes. Previous evidence also contradicted with each other when investigating the survival outcomes of these patients [9][10][11][12] . The result of NASBP B-47 suggested that HER2-targeted therapy didn't produce effect on HER2 low breast cancer 13 and this subset was treated as luminal-like or triple negative subtype according to the hormone receptor (HR) status.…”
Section: Introductionmentioning
confidence: 91%